Enhancing Repeat Patronage: Service Quality And Brand Image As Predictors Of Customer Loyalty In A Luxury Resort - Triandani, Ni Ketut Asthi Dewanti; Sihombing, Irene Hanna H.; Witarsana, I Gusti Agung Gede (Institut Pariwisata dan Bisnis Internasional, 2025)
In the competitive luxury hospitality industry, customer loyalty remains a critical determinant of sustainability. However, The Laguna, a luxury resort in Bali, has experienced a marked decline in repeat patronage despite substantial renovations, highlighting an unresolved gap between service delivery and brand promise. While previous studies have established links between service quality, brand image, and loyalty, research focusing on their interplay in the luxury resort segment under conditions of declining repeat visits remains limited. This study addresses this research gap by examining their combined and relative effects on customer loyalty at The Laguna. This study employed a quantitative survey design involving 90 repeat guests at The Laguna. Service quality was assessed using the SERVQUAL framework, while brand image and customer loyalty were measured through validated indicators. Multiple linear regression analysis was applied to test the hypotheses and evaluate the extent of influence.The results indicate that both service quality (β = 0.579, p < 0.001) and brand image (β = 0.244, p = 0.030) exerted significant and positive effects on customer loyalty. Service quality demonstrated the stronger influence, particularly through assurance, although reliability emerged as a weakness requiring managerial focus. Brand image, especially its uniqueness dimension, also contributed meaningfully, suggesting strategic opportunities for promotional enhancement. Collectively, these variables accounted for 62.1% of the variance in customer loyalty. The findings highlight the dual importance of service quality and brand image in sustaining loyalty within luxury resorts. For practitioners, the study underscores the urgency of enhancing reliability in service delivery and leveraging brand uniqueness through targeted promotional strategies. Theoretically, this research contributes to loyalty studies by contextualizing the service quality–brand image nexus within the luxury resort segment, offering insights for both scholars and managers concerned with improving guest retention.